Ambivalent Conspirators : John Brown, the Secret Six, and a Theory of Slave Violence - Rossbach, Jeffrey (University of Pennsylvania Press, 2016)
The remarkable relationship among the six conspirators who aided John Brown in his famed 1859 raid at Harpers Ferry is dramatically exposed in this volume. Why did these six abolitionists, who were nominally pacifist, decide to subsidize an act of black violence?.